+0  
 
0
591
2
avatar+33 

(4.92*10^-2)/(2.2*10^-4)

 Nov 28, 2014

Best Answer 

 #2
avatar+118604 
+10

(4.92*10^-2)/(2.2*10^-4)

 

$$\\\frac{4.92\times 10^{-2}}{2.2*10^{-4}}\\\\
=\frac{4.92}{2.2}\times \frac{10^{-2}}{10^{-4}}\\\\
=2.2\dot3\dot6\times 10^{-2--4}\\\\
=2.2\dot3\dot6\times 10^{-2+4}\\\\
=2.2\dot3\dot6\times 10^{2}\\\\$$

 Nov 28, 2014
 #1
avatar+128393 
+5

(4.92*10^-2)/(2.2*10^-4)   rewrite as

(4.92 / 2.2) * (10^-2/10^-4)  

(2.2363636363636364) * (10^4 / 10^2)     negative exponents "travel" across the fraction bar

2.2363636363636364 * 10 ^2   (in scientific notation)

or just

223.63636363636364

 

 Nov 28, 2014
 #2
avatar+118604 
+10
Best Answer

(4.92*10^-2)/(2.2*10^-4)

 

$$\\\frac{4.92\times 10^{-2}}{2.2*10^{-4}}\\\\
=\frac{4.92}{2.2}\times \frac{10^{-2}}{10^{-4}}\\\\
=2.2\dot3\dot6\times 10^{-2--4}\\\\
=2.2\dot3\dot6\times 10^{-2+4}\\\\
=2.2\dot3\dot6\times 10^{2}\\\\$$

Melody Nov 28, 2014

2 Online Users

avatar